Pengaruh Terapi Musik Dan Terapi Murottal Alquran Secara Audiovisual Terhadap Peningkatan Kekuatan Otot Dan Penurunan Kecemasan Pada Pasien Stroke Menjalani Latihan ROM Pasif Di Ruang Unit Stroke RSUD Dr. Soedomo Trenggalek - Ixora Ixora; Dewi Wulandari; Rahayu Niningasih (Jurnal Keperawatan Terapan, 2023)
Strokes can have an impact on various body functions, one of which is paralysis or problems controlling movement associated with muscle strength. These conditions can lead to discharge in stroke patients. One of the distraction techniques that can be used is Murottal Al-Quran. Murotal therapy which aims to help express feelings, assist with physical rehabilitation, have a positive effect on conditions, moods and emotions and reduce the level of feelings in patients. The aim of this study was to analyze the effect of music therapy and murrotal therapy audiovisual on increasing strength and reducing reduction in stroke patients undergoing ROM exercises in the Unit Stroke room of Dr. Soedomo. The research was carried out in the Unit Stroke room of Dr. Soedomo. Quasy Experiment research design with control group pretest-posttest design. The independent ROM therapy research variables and Al-Qur'an murottal music therapy, the dependent variable increased muscle strength and decreased reduction in stroke patients. The study population was all post-stroke patients at dr. Soedomo Trenggalek. The sampling technique used purposive sampling with a sample size of 30 people. Data were analyzed using independent sample t test and paired sample t test. The results obtained: There is a difference in the strength of the right hand muscle between before and after ROM exercise (p value 0.473> 0.05), there is no difference in left hand muscle strength between before and after ROM exercise (p value 0.493> 0.05), no There was a difference in right leg muscle strength between before and after ROM training (p value 0.772> 0.05), there was no difference in left leg muscle strength between before and after ROM training (p value 0.168> 0.05). As for anxiety, it was found that there was a difference in anxiety between before and after ROM therapy (p value 0.772> 0.05). There is a difference in right hand muscle strength between before and after ROM exercise and music murrotal Al-Quran therapy (p value 0.000 <0.05), there is a difference in left hand muscle strength between before and after ROM training and music murrotal Al-Quran therapy (p. value 0.000 <0.05), there is a difference in right leg muscle strength between before and after ROM training and Al-Quran murrotal music therapy (p value 0.000 <0.05), there is a difference in left leg muscle strength between before and after ROM training and music therapy murrotal Al-Quran (p value 0.000 <0.05). As for anxiety, it was found that there was a difference in anxiety between before and after ROM therapy and murrotal Al-Quran music therapy (p value 0.000 <0.05). There was a difference in right hand muscle strength between ROM exercises and Al-Quran murrotal music therapy (p value 0.000 <0.05), there was a difference in left hand muscle strength between ROM exercises and Al-Quran murrotal music therapy (p value 0.000 <0.05). ), there is a difference in right leg muscle strength between ROM exercises and music therapy murrotal Al-Quran (p value 0.000 <0.05), there is a difference in left leg muscle strength between ROM exercises and Al-Quran murrotal music therapy (p value 0.000 <0 , 05). As for anxiety, it was found that there was a difference in anxiety between ROM therapy and Murrotal Al-Quran music therapy (p value 0.000 <0.05).